2013
DOI: 10.3892/ijmm.2013.1437
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of decoy receptor 3 (DcR3) expression by siRNA in pancreatic carcinoma cells induces Fas ligand-mediated apoptosis in vitro and in vivo

Abstract: Abstract. Decoy receptor 3 (DcR3) is abundantly expressed in human tumors and protects cells from a wide range of apoptotic stimuli. In this study, we demonstrate that DcR3 is overexpressed in pancreatic carcinoma cells, and that the pancreatic carcinoma cell lines, Panc-1 and SW1990, are resistant to Fas ligand (FasL)-mediated apoptosis. To further define the function of DcR3 in cell growth and apoptosis, we used small interfering RNA (siRNA) to knockdown the expression of the DcR3 gene in Panc-1 and SW1990 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The expression of DcR3 protein was detected in various types of malignant tumors by our and other groups, especially in glioma, gastric, breast, liver and pancreatic cancer (Chen and Luo, 2008a;2008b;Chen et al, 2010;Huang et al, 2014;Wu et al, 2014;Zhou et al, 2014). DcR3 is also closely related to the occurrence, development and prognosis of various malignant tumors (Yang et al, 2010;Toda et al, 2013;Zhou et al, 2013;Wu et al, 2014;Zhou et al, 2014). Moreover, it is absent or lowly expressed in normal tissues except cancerization.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The expression of DcR3 protein was detected in various types of malignant tumors by our and other groups, especially in glioma, gastric, breast, liver and pancreatic cancer (Chen and Luo, 2008a;2008b;Chen et al, 2010;Huang et al, 2014;Wu et al, 2014;Zhou et al, 2014). DcR3 is also closely related to the occurrence, development and prognosis of various malignant tumors (Yang et al, 2010;Toda et al, 2013;Zhou et al, 2013;Wu et al, 2014;Zhou et al, 2014). Moreover, it is absent or lowly expressed in normal tissues except cancerization.…”
Section: Discussionsupporting
confidence: 51%
“…DcR3 can block LIGHT, FasL and TL1A mediated cell apoptosis and proliferation (Aiba et al, 2013;Fukuda et al, 2013;Toda et al, 2013;Zhou et al, 2013). To further investigate the potential mechanism of DcR3 to influence the biological function of BUC, we compared the DcR3 expression and other common biomarkers, including caspase-3, Bcl-2, VEGF, Ki-67 and PCNA labeling indexes (LIs) and P53.…”
Section: Discussionmentioning
confidence: 99%
“…FasL-resistant cells expressed higher levels of several anti-apoptotic genes than FasL-sensitive cell lines, and lower levels of several pro-apoptotic genes. We previously reported that depletion of DcR3 could inhibit tumor cell growth and proliferation in pancreatic cancer cells [29], so selected DcR3 for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that depletion of DcR3 could inhibit pancreatic cancer cell growth and proliferation [29]. However expression of DcR3 and its downstream signaling in pancreatic cancer patients has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) (ICAM-1 was not included in the analysis), suggesting that the NF-κB signaling pathway regulates the immune response in the tumor microenvironment of SI-NETs. Knockdown of DcR3 in vivo (in mice xenografts) inhibited pancreatic cancer tumor growth, demonstrating the importance of this protein in cancer progression and suggesting that DcR3 is a potential therapeutic target [27] . Different treatments have been shown to reduce high concentrations of DcR3 in pancreatic adenocarcinoma cells (a tyrosine kinase and a PI3K inhibitor, an NF-κB inhibitor, and an insulin-like growth factor 1 inhibitor) [28] , indicating potential new treatment options also in SI-NETs.…”
Section: Discussionmentioning
confidence: 99%